An assessment of Lime, Alum and Activated Carbon in Purifying Peat Water for Clean Water - Yulintine, Yulintine; Harteman, Edison; Picierwatie, Picierwatie; Winanti, Maria Anashasia; Torang, Inga; Bungas, Kartika; Nasir, Darmae; Elvince, Rosana (Universitas Gadjah Mada, 2025)
Central Kalimantan has a large area of peatland that contains a lot of peat water, which can be used as a source of clean water and drinking water. Meanwhile, the community still lacks clean water because peat waters are acidic to highly acidic, corrosive, and reddish-black, making them unsuitable for human use. Therefore, efforts are needed to purify peat water to be suitable for human consumption. This study aimed to assess the effectiveness of using calcium carbonate lime, alum, and activated carbon to purify peat water. This research was divided into 2 stages, namely preliminary research by testing the combination of the three materials mentioned above with the dose of each material, 0.3 g/L, 0.6 g, and 0.9 g/L, so that 33 treatments were obtained, namely 27 treatments. Test parameters in preliminary research are pH, water colour, and water appearance. In the main research, the observed variables were pH, water colour, TDS, and the appearance of water. In the main study, the best 6 treatments from the preliminary study were used, where the pH value was close to normal, ranging from 5.76 to 6.16, and the colour value ranged from 4 to 15 Pt-Co, and there was no foam. The best 3 main research results carried out complete testing of physical, chemical and microbiological water quality parameters for clean water, namely physical parameters (colour, odour, taste, turbidity, temperature, and TDS), chemistry (organic matter, pH, hardness, iron, manganese, sulphate, nitrite, chloride, nitrate, zinc, cyanide, fluoride, ammonia, aluminium and copper), and microbiology (total coliform and E. coli). Based on the results obtained, in the main study, the use of a combination of calcium carbonate lime, alum, and activated carbon at doses of 0.3 g/L, 0.3 g, and 0.6 g/L respectively was very effective in purifying peat water into water suitable for human consumption, so these doses are recommended for purifying peat water.